Effects of chronic treatment with soy derived Isoflavones on reproductive health of male rabbits - Cardoso, Júlio Roquete (2007)
The aim of this study was to investigate the effects of chronic exposure to soy isoflavones concentrate on the morphology of reproductive organs, semen quality, puberty age, serum levels of testosterone and sexual behavior of male rabbits. With this purpose, pregnant female rabbits were randomly assigned to receive orally 2.5mg (ISF 2.5) or 10mg (ISF 10) of soy isoflavones/kg of body wt/day. The animals of control group were manipulated as the other groups and received placebo (corn starch). All the rabbits were maintained on a soy-and alfafa-free diet throughout the gestation and lactation. Their male offspring received the same treatments from weaning to 33 weeks of age. Chronic exposure to isoflavones did not induce statistically significant alteration in the age at puberty, semen volume, daily sperm output, sperm concentration, motility, vigor and abnormalities. Also, isoflavones exposure had no effects on serum testosterone levels or sexual behavior in any group. Histopathologic evaluation did not reveal alterations in the testis, epididymis, prostate and pro-prostate glands of the rabbits. Taken together, these results show that gestational, lactational and post-lactational exposure to soy isoflavones, in doses comparable to those found in soy-containing animal and human diets, has no adverse effects on the reproductive parameters of male rabbits.